Negotiating professional authority and power in tourist–guide communication in guided village tour. (13th November 2020) - Sharma, Bal Krishna
Abstract: The article examines the linguistic, material, and multimodal aspects of professional communication in guided tours in the Himalayas in Nepal. Using an ethnography‐informed interactional sociolinguistics, the study analyses the key instances of miscommunication between an American tourist and an ethnic Tamang guide to understand how various identities are invoked by the participants. As the article considers the complexity of working for tourists in the second language in which a worker's competence is questioned, it also recognizes the importance of a range of semiotic resources that tour guides deploy to negotiate professional authority with tourists. Overall, the findings show how individuals manage interpersonal relations and expertise in transnational workplaces to contest and reconstruct dominant social positions and achieve their interactional goals. सार: यस लेखले नेपालको हिमालय क्षेत्रमा पथप्रदर्शक सहितको यात्रामा हुने व्यावसायिक संचारको भाषिक, भौतिक र बहुमोडल पक्षहरूको अध्ययन गर्दछ। एथ्नोग्राफी‐सूचित अन्तरक्रियामूलक सामाजिक‐भाषाविज्ञानको प्रयोग गरेर सहभागीहरूले विभिन्न पहिचानहरू कसरी सम्वोधन गरिरहेका छन् भनेर बुझ्नका लागि यो अध्ययनले एक अमेरिकी पर्यटक र तामाङ गाईडबीचको अपसंवादको मुख्य घटनाहरूको विश्लेषण गर्दछ। लेखले पर्यटकहरूको लागि दोस्रो भाषामा काम गर्ने जटिलतालाई विचार गर्दै एक पर्यटकीय पथप्रदर्शक श्रमिकको क्षमतामाथि कसरी प्रश्न खडा हुन्छ र उक्त श्रमिकले पर्यटकहरूसँग प्रोफेसनल अधिकारको लागि कसरी सेमिओटिक स्रोतहरूको प्रयोग गर्दछ भन्ने कुरालाई मान्यता दिन्छ। समग्रमा यो लेखले प्रभावशाली सामाजिक स्थानहरुको पुनर्संरचना गर्न र उनीहरुका अन्तर्क्रियात्मक लक्ष्यहरु लाई प्राप्त गर्नका लागि ट्रान्स्नेशनल कार्यस्थलहरुमा कसरी व्यक्तिहरु विशेषज्ञता र सामाजिक सम्बन्धहरुलाई व्यवस्थापन गर्छन् भन्ने कुरा देखाउँछ।